Cooperation in Cooperatives The Creation, Diffusion and Realisation of Ideas - Frisch, Johan (My University, 2019)
The topic of this master’s thesis is the creation, diffusion and realisation of ideas in cooperatives. The aim is to investigate how this is done at cooperatives. Cooperatives are democratic organisations were members share an equal vote in the decision making. This study focuses on cooperatives were the workers have the right to apply for membership. Gathering of data was done with interviews. Two cooperatives in Gothenburg, Sweden were selected in the study. The study finds that some cooperative-specific methods were used for the creation, diffusion and realisation of ideas. Furthermore, quantified computer simulations are a potential way of analysing and improving the structure of cooperatives.
Keywords: Transport; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Övrig industriell teknik och ekonomi; Transport; Sustainable Development; Innovation & Entrepreneurship; Other industrial engineering and economics